Analisis Peran Person-Organization Fit, Person Job Fit, dan Work-Life Balance Terhadap Organizational Citizenship Behavior Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Andrean Maulana; Olivia Fachrunnisa (eCo-Fin, 2026)
This research looks at how Person-Organization Fit, Person-Job Fit, and Work-Life Balance affect Organizational Citizenship Behaviour, and also examines how job satisfaction plays a role in connecting these factors. The study was carried out on the staff members of Bank BRI's Pattimura Branch in Semarang. This study used a quantitative method by giving questionnaires to a group of people who were chosen through a probabilistic sampling technique. Data processing used a method called Partial Least Squares based Structural Equation Modelling. This study aims to explore how the match between employees and the organization, the suitability of their jobs, and the balance between work and personal life can lead to employees taking positive actions that help the organization work better. The study also wants to find out how job satisfaction affects the connections between these three factors and organizational citizenship behaviour. This study looks at how well a person matches with their organization, how well their job fits their skills and interests, and how balanced their work and personal life is, and how these factors can lead to employees showing positive behaviour that goes beyond what is required in their official job role. By learning how these variables connect, the study aims to help create better ways to manage people in the banking industry.